PERANCANGAN VISUAL BRANDING PRODUK HOT PANGSIT NYONYOR - Ilham Joni Saputra, San Ahdi, M.Sn., M.Ds. Dra. Zubaidah, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Hot Pangsit also known as spicy snacks that develop in the Kota Jambi, Hot Pangsit Nyonyor is the first hot pangsit found in Padang. The visual identity is not maximal and still has no brand image or distinctive characteristics, so that the target audience of Hot Pangsit Nyonyor does not know the brand of the product. Hot Pangsit Nyonyor needs a visual branding design in order to enhance the brand image of the product, so that in the future it can reach a wider target market. The purpose of the design is to build brand awareness of Hot Pangsit Nyonyor, products which are expected to have a positive image in the minds of consumers. The method used is Design Thingking with 5W + 1H analysis (what, who, where, when, why and how) to solve the problems of product. The design produced the Manual Book design as the main media, and several supporting media, namely: business cards, seals, envelopes, letters, paper bags, aprons, paper wraps, t-shirts, stickers, posters, x-banners, and banners.Key Words : Visual Branding, Hot Pangsit, Brand